From internal brand management to organizational citizenship behaviours: Evidence from frontline employees in the hotel industry. (December 2016) - Buil, Isabel; Martínez, Eva; Matute, Jorge
Abstract: This paper examines the links between internal brand management, organizational identification, work engagement, and organizational citizenship behaviours in the hospitality industry. A model is proposed and tested using a sample of 323 frontline employees from the main hotel chains operating in Spain. This model includes different dimensions of internal brand management and different manifestations of citizenship behaviours. Data are analysed through the use of partial least squares. The findings confirm that transformational leadership leverages organizational identification and work engagement. However, brand training and brand communications do not directly raise positive emotions in the workplace. The results also suggest that work engagement is a better predictor of citizenship behaviours than organizational identification. Identification influences citizenship behaviours towards the organization. However, this variable does not explain extra-role supportive behaviours towards customers and other employees. These results extend previous research by empirically analysing the effects of internal brand management from the employees' perspective. Highlights: Internal brand communications and training enhance employees' organizational identification. Transformational leadership has a stronger impact on organizational identification than on work engagement. Organizational identification only predicts citizenship behaviors towards an organization. Work engagement positively affects all organizational citizenship dimensions.